Exposure to Atrazine through gestation and lactation period led to impaired sexual maturation and subfertility in F1 male rats with congenital deformities in F2 progeny. (November 2021) - Pandey, Neelam; Maske, Priyanka; Mote, Chandrashekhar; Dighe, Vikas
Abstract: Several scientific reports suggest perturbed reproductive and developmental defects associated with environmental exposure to Atrazine (ATR). ATR has been associated with altered endocrine and reproductive functioning in-vivo exposed during the critical window of development. Thus, the present study investigates the effect of ATR exposure on F1–F2 male progeny exposed through gestation and lactation. F0 dams administered with ATR at doses 2, 10, 70, and 100 mg/kg b. wt/day from gestation day 6 to postnatal day 21. The F1 male rats were monitored for sexual maturation and subjected to fertility assessment on PND75. Delayed testicular descent was observed in 10, 70, and 100 mg/kg b. wt/day ATR dose with significantly lower serum testosterone, sperm count, and motility with testicular defects in F1 male. Expression of Androgen receptor (AR), Estrogen receptors (ER α and ER β), StAR, Aromatase, and INSL-3 were upregulated at all doses indicating estrogenic/anti-androgenic activity of ATR. Fertility assessment revealed subfertility in F1 males with high (%) pre- and post-implantation loss at 10, 70, and 100 mg/kg b. wt/day dose as compared to control. Further, F2 fetuses exhibited congenital disabilities viz. decreased weight, crown-rump length, and anogenital distance with several other morphological deformities. To conclude, ATR exerted estrogenic and/or anti-androgenic activity with fetotoxic effects through the male germline. Graphical abstract: Image 1 Highlights: Maternal ATR exposure through gestation and lactation period caused delayed testis descent and altered steroid hormone homeostasis in F1 male rats. Maternal ATR exposure through the gestation and lactation period reduces sperm count, sperm motility, and disrupts testicular architecture in F1 rats during adulthood. ATR exerted estrogenic and/or anti-androgenic effects resulted in perturbed expression of steroidogenic genes or steroid hormone receptors in F1 males during adulthood. ATR exhibited fetotoxic and teratogenic effects that led to implantation losses, fetal resorption, and congenital disabilities in F2 generation.